Capital Structure and Sacco Growth: A Systematic Literature Review and Meta-Analysis - Milambo, Fidelity; Haabazoka, Lubinda; Mwanaumo, Erastus (Advances in Social Sciences Research Journal, 2023)
Globally, countries are paying particular attention to the potential of Savings and Credit Cooperative Organizations (SACCOs) as one form of enterprise with a meaningful impact on the economic empowerment of their citizens. Despite the growth of SACCOs being sparsely distributed across various countries, the growth of SACCOs driven by Capital Structure remains largely under-researched. Therefore, this paper seeks to address this problem and develop new insights into future research around SACCO growth and Capital Structure, through a systematic literature review and meta-analysis of 17 articles, thereby problematizing the literature reviewed. The analysis utilizes secondary data from 17 peer-reviewed journals selected using renowned research databases including Google Scholar, Semantic Scholar, and Base, for the period 2011 to 2021. Findings show that 70.6% of articles were published in the last 4 between 2021 - 2018, while 29.4% were published between 2017 – 2011. Kenya accounted for the majority of articles at 58.8%, while the rest of Africa had 17.6% of articles, Europe accounted for 17.6% and Asia 5.9%. Financial performance was prominent at 48.4% as a major parameter in the measurement of SACCO growth, with capital structure at 35.5%, capital adequacy at 9.7%, and growth at 6.5%. The review found that all 17 articles that were analyzed lacked in the area of modeling the relationship between the study variables of capital structure and SACCO growth. A review and analysis of all 17 articles showed that none of the studies directly focused on capital structure and its impact on SACCO growth.